JIRA 7 essentials : explore the great features of the all-new JIRA 7 to manage projects and effectively handle bugs and software issues - Li, Patrick, 1983- (Packt Publishing, 2016)
Explore the great features of the all-new JIRA 7 to manage projects and effectively handle bugs and software issues About This Book Updated for JIRA 7, this book covers all the new features introduced in JIRA 7 with a dedicated chapter on JIRA Service Desk - one of the biggest new add-ons to JIRA This book lays a strong foundation to work with agile projects in JIRA from both the administrator and end user's perspective Work through step-by-step exercises at the end of each chapter for you to try out and reinforce your skills Who This Book Is For This book will be especially useful for project managers but it's also intended for other JIRA users, including developers, and any other industry besides software development, who would like to leverage JIRA's powerful task management and workflow features to better manage their business processes. What You Will Learn Understand JIRA's data hierarchy and how to design and work with projects in JIRA Plan and set up a new JIRA 7 instance from scratch for production use Using JIRA for agile software projects, business process management, customer service support, and more Understand issues and work with them Design both system and custom fields to behave differently under different contexts Create and design your own screens and apply them to different project and issue types Gain an understanding of the workflow and its various components Set up both incoming and outgoing mail servers to work with e-mails In Detail Atlassian JIRA is an enterprise-issue tracker system. One of its key strengths is its ability to adapt to the needs of the organization, ranging from building Atlassian application interfaces to providing a platform for add-ons to extend JIRA's capabilities. JIRA 7 Essentials, now in its fourth edition, provides a comprehensive explanation covering all major components of JIRA 7, which includes JIRA Software, JIRA Core, and JIRA Service Works. The book starts by explaining how to plan and set up a new JIRA 7 instance from scratch for production use before moving on to the more key features such as e-mails, workflows, business processes, and so on. Then you will understand JIRA's data hierarchy and how to design and work with projects in JIRA. Issues being the corner stone of using JIRA, you will gain a deep understanding of issues and their purpose. Then you will be introduced to fields and how to use custom fields for more effective data collections. You will then learn to create new screen...